(untitled) (Simbiótica. Revista Eletrônica, 2023)
This article intends to discuss the recent use of quantitative data by the LGBTI+ movement to claim citizenship. From a variety of materials, such as reports produced by the Grupo Gay da Bahia (GGB), the Associação Nacional de Travestis e Transexuais (ANTRA) and the Movimento por Avanço nas Políticas Públicas de Atenção às Populações LGBTI+ (MAPPA LGBTI+), I propose the use of "LGBTI+ statactivism" to understand such strategies. In the first section, I present a brief recovery from the construction of gender and sexuality categories. In the second, I discuss how state measurements produce certain citizens in their official quantifications. In the last two sections I present the initiatives of the LGBTI+ movement mentioned above.